m6A demethylase CpALKBH regulates CpZap1 mRNA stability to modulate the development and virulence of chestnut blight fungus - Lijiu Zhao; Xiangyu Wei; Fengyue Chen; Baoshan Chen; Ru Li (mBio)
ABSTRACT As the most abundant eukaryotic mRNA modification, N6-methyladenosine (m6A) plays a crucial role in regulating multiple biological processes. This methylation is regulated by methyltransferases and demethylases. However, the regulatory role and mode of action of m6A demethylases in fungi remain poorly understood. In this study, we demonstrate that CpALKBH is a demethylase in Cryphonectria parasitica that removes m6A modification from single-stranded RNA in vitro. The deletion of CpALKBH resulted in a significant increase in the m6A methylation levels, along with decreases in the growth rate, sporulation, and virulence in C. parasitica. Additionally, CpZap1—a transcription factor—was identified as a downstream target of CpALKBH demethylase based on RNA sequencing analysis. We confirmed that CpALKBH demethylase regulates CpZap1 mRNA stability in an m6A-dependent manner. Furthermore, through MazF assay, we found that methylation of CpZap1 at position 1935A is regulated by both CpALKBH demethylase and CpMTA1 methyltransferase. CpZap1 significantly influences the fungal phenotype and virulence, thereby restoring the abnormal phenotype observed in ∆CpALKBH mutants. Collectively, our findings highlight the essential role of CpALKBH as an m6A demethylase in the development and virulence of C. parasitica, while also elucidating the molecular mechanisms through which m6A modification impacts CpZap1 mRNA stability.IMPORTANCEN6-methyladenosine (m6A) is the most abundant eukaryotic mRNA modification and is involved in various biological processes. Methyltransferases and demethylases regulate the m6A modification, but the regulatory role of m6A demethylases in fungi remains poorly understood. Here, we demonstrated that CpALKBH functions as a demethylase in Cryphonectria parasitica. The deletion of CpALKBH leads to a significant increase in m6A levels and a reduction in fungal growth, sporulation, and virulence. We identified CpZap1 as a downstream target of CpALKBH, with CpALKBH regulating CpZap1 mRNA stability in an m6A-dependent manner. Additionally, our findings indicate that methylation at position 1935A of CpZap1 is regulated by both the CpALKBH demethylase and the CpMTA1 methyltransferase. Given its critical role in fungal development and virulence, overexpression of CpZap1 can rescue abnormal phenotypes of ∆CpALKBH mutant. Overall, these findings contribute to improving our understanding of the role of m6A demethylase in fungi.